1999
DOI: 10.3109/02841859909175578
|View full text |Cite
|
Sign up to set email alerts
|

Hypoperfusion in the Renal outer Medulla after Injection of Contrast Media in Rats

Abstract: Iso-osmolar and high-osmolar contrast media (CM), at normal and high doses, decrease OMBF, while an extremely high dose of iothalamate may result in an increase. The depression of outer medullary perfusion may have implications for CM-induced acute renal failure in view of the vulnerability of this region to a decrease in oxygen tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
2
13
0
4
Order By: Relevance
“…This group of researchers (24) noted a similar decline in outer medullary regional blood flow, using both laser Doppler needle probes and hydrogen washout techniques; however, at very high volumes of injected radiocontrast, outer medullary regional microcirculation markedly increased (25)(26)(27), as long as NO or prostaglandin synthesis remained intact (25). Thus, so far, the impact of radiocontrast on outer medullary perfusion remains a matter of debate, with the different patterns of response possibly related to the type, volume, and route of administration of the dye.…”
Section: Radiocontrast-induced Decrease In Renal Oxygen Supplymentioning
confidence: 99%
“…This group of researchers (24) noted a similar decline in outer medullary regional blood flow, using both laser Doppler needle probes and hydrogen washout techniques; however, at very high volumes of injected radiocontrast, outer medullary regional microcirculation markedly increased (25)(26)(27), as long as NO or prostaglandin synthesis remained intact (25). Thus, so far, the impact of radiocontrast on outer medullary perfusion remains a matter of debate, with the different patterns of response possibly related to the type, volume, and route of administration of the dye.…”
Section: Radiocontrast-induced Decrease In Renal Oxygen Supplymentioning
confidence: 99%
“…The RCM-induced decrease in partial oxygen pressure (PaO 2 ) is marked in the outer medulla where thick ascending limbs of Henle's loop exist and PaO 2 depends largely on the activities of electrolytes transport systems located on renal tubular membranes (8,51). It has been demonstrated that several loop diuretics, including furosemide, reduce oxygen consumption by inhibiting Na…”
Section: Effects Of Several Drugs For Prevention Of Radiocontrast Nepmentioning
confidence: 99%
“…Although little is known about cellular mechanisms underlying radiocontrast nephropathy, direct toxic action on renal tubular cells (renal mechanism) (4 -7) and / or decrease in renal blood flow (pre-renal mechanism) (8,9) have been considered to be involved in the pathogenesis of radiocontrast nephropathy. A number of compounds that improve renal blood flow have been clinically tested for prevention of radiocontrast nephropathy, but most of them were not effective.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios con animales han documentado una constricción de los vasos rectos que irrigan la médula externa debida al contraste, y un descenso en el flujo sanguíneo medular, ratio de filtración glomerular, velocidad de los hematíes y de la tensión de oxígeno, junto a un incremento en la agregación de los hematíes (32)(33)(34)(35) . En otro estudio animal, la administración intra-arterial de contraste causa una respuesta bifásica, con un período corto de tiempo de hiperperfusión seguido de vasoconstricción con la consecuente hipoperfusión y, finalmente, restauración del flujo normal en unos minutos (36) .…”
Section: Fisiopatología De La Nefropatía Asociada a Contrasteunclassified
“…En nuestra serie, obtenemos una incidencia de NAC del 13.7% en aquellos pacientes que presentan al menos un factor de riesgo, frente al 8.4% de pacientes que no presentaban ninguno. La administración de diuréticos se relacionó con una mayor incidencia de NAC, probablemente por favorecer la hipoperfusión renal secundaria a hipovolemia, que podría contribuir, junto con la hipoperfusión renal generada por el contraste, al desarrollo de esta entidad (32)(33)(34)(35)(36) . Debemos recordar que la disminución de la perfusión renal ha sido postulada, en el estudio de Nash et al como el principal factor de riesgo de lesión renal aguda en pacientes hospitalizados (52) .…”
Section: Características Diferenciales De Los Pacientes Coronariosunclassified